The factors influencing SME failure in South Africa - Leboea, Sekhametsi Tshepo (Research of GSB, 2017)
Like many developing countries, South Africa faces a great development problem relating to the high failure rate that is present among Small and Medium Enterprises (SMEs), this is due to the fact that entrepreneurs are not able to turn their businesses into sustainable venture. SMEs play a significant role is a number of economic development issues that face South Africa as a nation. The SME sector has contributed immensely to job creation, poverty alleviation and assisting in the prosperity of the nation. In addition to the above, SMEs are generally inexpensive to start and have the potential to generate massive economic growth in South Africa. Although the SME sector has many positive attributes, there are persisting challenges that plague South African SMEs. Fatoki and Garwe (2010) state that in the South African context, new SMES do not usually move from the existence stage, which is the first stage of growth, to the subsequent stages such as survival, success, take off and resources maturity. As such, it is believed that many of these SMEs do not survive in their first years of operation and thus, do not provide their benefits to society.